On brief history of Amarbayasgalant lamasery and its current state - Бүрнээ, Д. (Acta Mongolica, 2004)
The Amarbayasgalant as one of valued monuments of Mongolian ancient history and culture was built in 1727-1736 in the south side of mountain Burenkhan, Selenge aimag. It was founded by decree of Manchu emperor Yongzheng in honour of Mongolian First Bogdo Jabtsandamba Khutugtu Zanabazar (1635-1723). The First Bogdo Jabtsandamba was famous religious and state figure, enlightener, who played an important role in spreading of Buddhism in Mongolia. In the half past of 19th century, when Buddhism was spreading in Mongolia famous Russian traveller A.M.Pozdneyev during 1892-1893 had travelled in Mongolia and on the basis of his notes wrote a book "Mongolia and Mongols". There is a note in this book about Amarbayasgalant, which he wrote from 2nd to 6th July of 18921. From this notes we can know appearence of former Amarbayasgalant lamasery. In that time Amarbayasgalant consisted of 8 datsans and 6 aimags. Only in Zoogai and Choinkhorlin aimags there were 500-600 lamas and other aimags had 250-300 lamas, alltogether this lamasery had over 2000 lamas. There were other datsans in that time.